Amitié sincère - Claudia Lindén (Tidskrift för Litteraturvetenskap, 2010)
Amitié Sincère – a Counter Narrative and a Story of Love Between Women. A Reading of Karen Blixen’s/Isak Dinesen’s »The Roads Round Pisa«